Multitasking Streetlight –A Novel System - Dr. Arpita Gupta; Bhawish Goel; Anas Ali Khan; Shyam Sharma, (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2024)
In today's era vehicle accidents are one of the leading causes of death due to lack of attention and help in time, poor emergency facilities, people lose their life. Highways are very vulnerable to accidents and many times the accident victims are unattended. Several time the accidents do not come under notice due to low traffic or ignorant trespassers. The Street light discussed in the paper is an automated system which witness the street throughout day and night. In case of any accident the streetlight will be able to generate an alarm as well as it will alert the concern authority. It simply observes the stay time of a vehicle in a pre-decided patch of road. In case of any delay, the streetlight will warn the concern team about the same. If there is an issue, the location is sent to the rescue team with the help of GSM module. The authors are also trying to reduce power consumption whenever there is no vehicle movement on the road. The streetlight will glow with high intensity when there is a vehicle on road otherwise it will be dim.